Recent approaches of antibody therapeutics in androgenetic alopecia - Jin, Su-Eon; Kim, Jino; Sung, Jong-Hyuk (Frontiers in Pharmacology, 2024)
Therapeutic antibodies (Abs) have been anticipated as promising alternatives to conventional treatments such as topical minoxidil and oral finasteride for androgenetic alopecia (AGA). Due to the high molecular weight of typical Abs, the halflife of subcutaneous Abs exceeds 2 weeks, allowing an administration intervals of once a month or longer. Direct injection into the areas of hair loss is also feasible, potentially enhancing treatment efficacy while minimizing systemic side effects. However, therapeutic Abs are rarely developed for AGA therapy due to the requirement to be responsiveness to androgens and to exist in the extracellular fluid or cell surface surrounding the hair follicle. In this review, we introduce recent progress of antibody therapeutics in AGA targeting the prolactin receptor, Interleukin-6 receptor, C-X-C motif chemokine ligand 12, and dickkopf 1. As therapeutic Abs for AGA are still in the early stages, targets need further validation and optimization for clinical application.